Preparation method of rubber composite material

By flocculating and copolymerizing the coal-gasified black water flocculant with rubber latex, rubber composite materials are prepared, which solves the problems of complex processes and high energy consumption in the existing technology, and realizes the preparation of rubber composite materials with short process flow, water-saving and environmentally friendly and low energy consumption.

CN119708659AActive Publication Date: 2025-03-28INNER MONGOLIA YIDONG GROUP JIUDING CHEMICAL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510214453.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-03-28
Estimated Expiration
2045-02-26

AI Technical Summary

Technical Problem

The existing technology has problems such as complicated process flow, high production energy consumption, and environmental pollution in the comprehensive utilization of coal gasified fine slag, and cannot effectively utilize the functional properties of coal gasified fine slag.

Method used

By concentrating, grinding, magnetic separation and alkalizing of coal gasified black water flocculant, the refined slurry and rubber latex are obtained for flocculation and copolymerization, and rubber composite material is prepared. This method has a short process flow, water conservation and environmental protection, and low energy consumption.

Benefits of technology

The effective utilization of coal gasified black water flocculant was achieved, and rubber composite materials with excellent mechanical properties were prepared, which solved the problems of complex processes and high energy consumption in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708659A_ABST
    Figure CN119708659A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of rubber materials, and particularly relates to a preparation method of a rubber composite material. According to the method, the coal gasification black water feed liquid at the front end of the coal gasification fine slag is creatively used as the raw material liquid to be directly subjected to functional modification; according to the method, water in the coal gasification black water feed liquid is fully utilized, centrifugal dewatering and direct drying of the coal gasification fine slag are avoided, functionalization treatment of the coal gasification fine slag and preparation of the powdered rubber are combined, and the method has the advantages of being short in technological process, low in cost and the like. The production energy consumption is low; the water is saved; the environment is protected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rubber materials, and in particular relates to a method for preparing a rubber composite material. Background Art

[0002] my country is a country with abundant coal resources, with coal production accounting for more than 50% of the world's total production. Coal occupies a dominant position in my country's energy structure. As my country's energy consumption structure accelerates its transformation towards clean and low-carbon, clean and efficient use of coal has become an inevitable trend. At present, coal gasification has become one of the key development directions for clean and efficient use of coal, which meets the requirements of green, low-carbon and high-quality development of my country's industry.

[0003] During the gasification process of coal, most of the carbonaceous components in the coal are converted into gas, while the associated inorganic minerals, carbonaceous materials that are difficult to gasify, and catalysts in the raw coal will be discharged in the form of residue, namely, coal gasification slag. Research and analysis results show that about 15-20% of the components of coal will be converted into gasification slag during the gasification process. At present, the comprehensive utilization rate of coal gasification ash is low, and landfill and open-air stacking are still the main methods. The long-term storage of huge amounts of gasification ash pollutes the soil / water system and the atmospheric environment, seriously threatening the safety of the ecological environment. The comprehensive treatment of coal gasification ash has become a prominent bottleneck restricting the green, low-carbon and sustainable development of the coal chemical industry. At present, the comprehensive utilization of coal gasification slag is mainly aimed at coal gasification fine slag, and the application research is mainly concentrated in the fields of recycling carbon components, building materials, soil improvement and water pollution control, but there are no large-scale, mature and full-component industrial utilization cases of coal gasification slag.

[0004] During the coal gasification process, the minerals and other components in the coal are transformed into slag. A part of the slag is carried out by the airflow and enters the subsequent purification process. Finally, it is discharged into the gray water treatment system with black water to form coal gasification black water flocculant. The black water flocculant is pumped and dehydrated to form fine slag with smaller particle size, which is called coal gasification fine slag. Coal gasification fine slag has the characteristics of high water content, mixed residual carbon and inorganic components, large component volatility and difficulty in dehydration; at the same time, the carbon and ash components restrict each other, which hinders its resource utilization. The carbonaceous component and inorganic silicon-aluminum glassy component in the coal gasification fine slag are a typical carbon-silicon hybrid material with stable physical and chemical properties, suitable specific surface area and high temperature resistance. After proper treatment, it can be used as a composite filler for polymer composite materials.

[0005] The prior art discloses a method for preparing rubber filler using coal gasification slag as raw material, which comprises subjecting the coal gasification fine slag to drying, magnetic separation, activation, ultrafine processing and surface modification to prepare rubber filler powder; the prior art also discloses a rubber filler using coal gasification fine slag as raw material, a preparation method and use thereof, which comprises removing residual carbon in the coal gasification fine slag, dissolving metal oxides by acid dissolution, and obtaining mesoporous silica filler; the prior art also discloses a preparation method for rubber and plastic filler, a rubber and plastic filler and use thereof, which comprises adding water to the coal gasification fine slag to make pulp, collecting silicon-rich composite slurry by gravity cyclone, and then performing solid-liquid separation and drying to obtain the rubber and plastic filler.

[0006] The existing technologies all collect gasification slag samples from the gasification slag yard and subject the gasification slag to a series of process treatments. The process flow from gasification slag to polymer composite products is long and complicated. The gasification slag needs to be treated with acid during the processing, which easily produces acid-containing wastewater, causing environmental pollution. The gasification slag needs to be dried during the processing. Due to the high water content and difficulty in dehydration of the gasification slag, the production energy consumption is high. At the same time, the existing processes all prepare the gasification slag into filler powder, and the filler powder needs to be reprocessed with rubber raw rubber. It is impossible to organically combine the functional treatment of the gasification slag with the preparation of rubber materials, resulting in a complicated and lengthy process flow for the application of the gasification slag in rubber-plastic composite materials.

[0007] Therefore, there is an urgent need for a treatment technology with a short process flow, water-saving, environmental protection and low energy consumption. Summary of the invention

[0008] The present invention is based on the carbon-inorganic component silicon composite structure in coal gasification black water flocculant, and aims to provide a method for preparing a rubber composite material using the carbon-inorganic component in the coal gasification black water flocculant. The method provided by the present invention has a short process flow, is water-saving and environmentally friendly, and has low energy consumption.

[0009] In order to achieve the above object, the present invention provides the following technical solutions: The present invention provides a method for preparing a rubber composite material, comprising the following steps: The concentrated liquid obtained by concentrating the coal gasification black water flocculation liquid is mixed with a dispersant, and then subjected to grinding and magnetic separation in sequence to obtain a magnetically separated suspension; The suspension after magnetic separation is adjusted to be alkaline, and then aged and sieved in sequence to obtain a refined slurry; The refined slurry, rubber latex and flocculant are mixed and flocculated to obtain the rubber composite material.

[0010] Preferably, the mass concentration of the concentrated solution is 15-45%; The dispersant includes one or more of sodium polyacrylate, sodium stearate, sodium hexametaphosphate, sodium tripolyphosphate and sodium citrate; The mass of the dispersant is 0.3-5.5% of the mass of the dry matrix of the concentrate.

[0011] Preferably, the grinding time is 10 to 120 minutes.

[0012] Preferably, the intensity of the magnetic separation is 800-1600 Gauss, and the time of the magnetic separation is 1-3 min.

[0013] Preferably, the alkaline pH value is 8.5-11.0; The aging temperature is 35-65° C.; the aging is carried out under stirring, and the stirring time is 0.5-1.5 h.

[0014] Preferably, the particle size D90 of the solid particles in the refined slurry is 2-18 μm.

[0015] Preferably, the rubber latex includes one or more of styrene-butadiene rubber latex, natural rubber latex and nitrile rubber latex; The mass concentration of the rubber latex is 40-69%; The mass ratio of the dry matrix of the refined slurry to the solid in the rubber latex is 1:1.5-10.

[0016] Preferably, the flocculant includes one or more of MgCl2, Mg(NO3)2, H2SO4, Mg(CH3COO)2, Al2(SO4)3 and KAl(SO4)2; The flocculant is mixed in the form of a flocculant solution, and the mass concentration of the flocculant solution is 15-20%.

[0017] Preferably, the flocculation copolymerization temperature is 35-70° C., and the flocculation copolymerization is carried out under stirring.

[0018] Preferably, after the flocculation copolymerization, the obtained materials are mixed and vulcanized in sequence.

[0019] The invention provides a method for preparing a rubber composite material, comprising the following steps: mixing a concentrated liquid obtained by concentrating coal gasification black water flocculation liquid with a dispersant, and sequentially performing grinding and magnetic separation to obtain a magnetically separated suspension; adjusting the magnetically separated suspension to be alkaline, and then sequentially performing aging and sieving treatments to obtain a refined slurry; mixing the refined slurry, rubber latex and a flocculant, and performing flocculation copolymerization to obtain the rubber composite material.

[0020] The present invention innovatively starts from the front end of coal gasification fine slag - coal gasification black water liquid, and uses it as the raw material liquid for direct functional modification; then the functionalized raw material liquid and rubber latex are prepared into powdered rubber material through emulsion co-coagulation method. This method makes full use of the moisture in the coal gasification black water liquid, avoids centrifugal dehydration and direct drying of the coal gasification fine slag, combines the functionalization treatment of the coal gasification fine slag with the preparation of powdered rubber, and has the advantages of short process flow, low production energy consumption, water saving and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 A schematic diagram of the preparation method provided by the present invention; Figure 2 This is the particle size distribution diagram of the original coal gasification black water flocculant; Figure 3 This is a particle size distribution diagram of the coal gasification black water concentrate after grinding obtained in Example 1; Figure 4 This is the particle size distribution diagram of the coal gasification black water concentrate after grinding obtained in Example 2; Figure 5 This is a particle size distribution diagram of the coal gasification black water concentrate after grinding obtained in Example 3; Figure 6 This is a particle size distribution diagram of the coal gasification black water concentrate after grinding obtained in Example 4; Figure 7 This is a particle size distribution diagram of the coal gasification black water concentrate after grinding obtained in Example 5; Figure 8 This is the particle size distribution diagram of the coal gasification black water concentrate after grinding obtained in Example 6; Fig. 9 This is the particle size distribution diagram of the coal gasification black water concentrate after grinding and stripping obtained in Comparative Example 1; Fig.10 This is the particle size distribution diagram of the coal gasification black water concentrate after grinding and stripping obtained in Comparative Example 2; Fig.11 This is the particle size distribution diagram of the coal gasification black water concentrate after grinding obtained in Comparative Example 3; Fig.12 This is a physical picture of the rubber compound powder obtained in Example 6; Fig.13 This is a physical picture of the rubber composite material obtained in Example 6; Fig.14 This is a SEM image of the rubber composite material obtained in Example 6; Fig.15 TEM image of the rubber composite material obtained in Example 6; Fig.16 This is the SEM image of the rubber composite powder obtained in Comparative Example 1. DETAILED DESCRIPTION

[0022] The present invention provides a method for preparing a rubber composite material, comprising the following steps: The concentrated liquid obtained by concentrating the coal gasification black water flocculation liquid is mixed with a dispersant, and then subjected to grinding and magnetic separation in sequence to obtain a magnetically separated suspension; The suspension after magnetic separation is adjusted to be alkaline, and then aged and sieved in sequence to obtain a refined slurry; The refined slurry, rubber latex and flocculant are mixed and flocculated to obtain the rubber composite material.

[0023] The invention mixes the concentrated liquid obtained by concentrating the coal gasification black water flocculation liquid with a dispersant, and sequentially performs grinding and magnetic separation to obtain a magnetically separated suspension.

[0024] In the present invention, the mass concentration of the concentrated liquid is preferably 15-45%. In the present invention, the concentration process preferably includes: subjecting the coal gasification black water flocculant to homogenization dispersion and sedimentation concentration in sequence. In the present invention, the mass concentration of the coal gasification black water flocculant is preferably 5-10%. The present invention has no special limitation on the source of the coal gasification black water flocculant, and those familiar to those skilled in the art can be used. The present invention has no special limitation on the process of homogenization dispersion and sedimentation concentration, and those familiar to those skilled in the art can be used.

[0025] In the present invention, the dispersant preferably includes one or more of sodium polyacrylate, sodium stearate, sodium hexametaphosphate, sodium tripolyphosphate and sodium citrate; the mass of the dispersant is preferably 0.3-5.5% of the mass of the dry matrix of the concentrate. In the present invention, the mixing is preferably carried out under stirring, and the stirring time is preferably 20-30 minutes.

[0026] In the present invention, the grinding time is preferably 10 to 120 minutes, more preferably 30 to 90 minutes. In the present invention, the grinding is preferably carried out in a wet vertical stirred mill. In the present invention, after the grinding, the particle size D90 of the solid particles in the obtained liquid is preferably 5 to 18 μm, and D50 is preferably 2 to 6 μm.

[0027] In the present invention, the intensity of the magnetic separation is preferably 800-1600 Gauss, more preferably 1000-1200 Gauss, and the time of the magnetic separation is preferably 1-3 min. In the present invention, the magnetic separation is preferably carried out in a high gradient magnetic separator.

[0028] After obtaining the magnetically separated suspension, the present invention adjusts the magnetically separated suspension to be alkaline, and then performs aging and sieving treatments in sequence to obtain a refined slurry.

[0029] In the present invention, the alkaline pH value is preferably 8.5 to 11.0, and more preferably 9 to 10. The present invention has no particular limitation on the adjustment process, and a method well known to those skilled in the art may be used.

[0030] In the present invention, the aging temperature is preferably 35-65° C.; the aging is preferably carried out under stirring, and the stirring time is preferably 0.5-1.5 h.

[0031] The present invention has no special limitation on the screening process, and a method known to those skilled in the art can be used. In the present invention, the particle size D90 of the solid particles in the refined slurry is preferably 2-18 μm. In the present invention, the mass concentration of the refined slurry is preferably 20-35%.

[0032] After obtaining the refined slurry, the present invention mixes the refined slurry, rubber latex and flocculant, and performs flocculation copolymerization to obtain the rubber composite material.

[0033] In the present invention, the rubber latex preferably includes one or more of styrene-butadiene rubber latex, natural rubber latex and nitrile rubber latex. In the present invention, the mass concentration of the rubber latex is preferably 40-69%, more preferably 40-50%. In the present invention, the mass ratio of the dry matrix of the refined slurry to the solid in the rubber latex is preferably 1:1.5-10.

[0034] In the present invention, the flocculant preferably includes one or more of MgCl2, Mg(NO3)2, H2SO4, Mg(CH3COO)2, Al2(SO4)3 and KAl(SO4)2; the flocculant is preferably mixed in the form of a flocculant solution, and the mass concentration of the flocculant solution is preferably 15-20%. The present invention has no special limitation on the mass of the flocculant, as long as flocculation is complete.

[0035] In the present invention, the temperature of the flocculation copolymerization is preferably 35-70° C. The flocculation copolymerization is preferably carried out under stirring. The present invention has no particular limitation on the time of the flocculation copolymerization, which can be carried out until the flocculation is terminated.

[0036] In the present invention, after the flocculation copolymerization, the obtained materials are preferably mixed and vulcanized in sequence. The present invention has no special limitation on the mixing and vulcanization process, and those skilled in the art can adopt the process well known to them.

[0037] In the present invention, after the flocculation copolymerization and before the mixing, the obtained material is preferably dehydrated, washed, dried and dispersed in sequence. The present invention has no special limitation on the dehydration, washing, drying and dispersion process, and the process well known to those skilled in the art can be adopted.

[0038] Figure 1 The present invention provides a schematic flow chart of the preparation method.

[0039] Figure 2 This is the particle size distribution diagram of the original sample of coal gasification black water flocculant. Figure 2 It can be seen that the particle size of the coal gasification black water flocculant is relatively large and the particle size distribution is relatively wide.

[0040] In the present invention, the particle size distribution is tested by ultrasonic laser particle size analyzer, ethanol is used as the solution, the material-alcohol mass ratio is 1:5, and the test is performed when the refractive index reaches 10-12.

[0041] In the present invention, the cross-sectional morphology is obtained by gluing the rubber composite material tensile cross-sectional sample onto a conductive adhesive, spraying gold, and observing the particle morphology and surface element distribution state on a field emission electron microscope with a resolution of 2.0nm (1kV, WD=1.5mm, normal mode); magnification: 1000-50000 times; electron gun: cold cathode field emission electron source.

[0042] In the present invention, the transmission electron microscope image test conditions are as follows: the maximum magnification is 1.1 million times, the acceleration voltage is 300kV; the point resolution is 0.20nm, the limit (information) resolution is 0.19nm, the minimum beam spot size is 0.2nm; the energy resolution of the X-ray spectrometer is 130eV.

[0043] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.

[0044] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] Example 1 200 kg of coal gasification black water flocculation liquid from a coal chemical enterprise in Ordos City was selected, and the mass concentration of the flocculation liquid was 7%; The coal gasification black water flocculated liquid is homogenized and dispersed and then concentrated by sedimentation to obtain a coal gasification black water concentrate having a mass concentration of 30%; Add dispersant sodium polyacrylate to the coal gasification black water flocculation liquid, the amount of dispersant added is 0.5% (0.07kg) of the dry matrix of the coal gasification black water flocculation liquid, and stir vigorously for 20 minutes; pump the stirred liquid to a wet vertical stirred mill, stir and grind for 30 minutes, and the particle size D90 of the solid particles in the milled liquid is 17.06μm and D50 is 5.04μm; pump the milled liquid to a high gradient magnetic separator for magnetic separation, the magnetic separation intensity is 1000 Gauss, the magnetic separation time is 3 minutes, and a suspension after magnetic separation is obtained; The pH value of the suspension after magnetic separation was adjusted to 9, and then stirred and aged at 35° C. for 0.5 h. The aged system was sieved to obtain 47 kg of refined slurry, in which the particle size of the solid particles in the refined slurry was D90 of 17.06 μm, and the mass concentration of the refined slurry was 30%; The refined slurry is pumped into a flocculation agitator, and then 70 kg of natural rubber latex (mass concentration is 40%) is added; a 20% mass concentration of Al2(SO4)3 flocculant solution is added through a peristaltic pump, and flocculation copolymerization is carried out by stirring at 60°C until flocculation stops; the obtained liquid is filtered, washed with water three times, dried, and then dispersed to obtain a rubber composite powder; The obtained rubber composite powder is sequentially mixed and vulcanized to obtain the rubber composite material; Figure 3 This is the particle size distribution diagram of coal gasification black water concentrate after grinding.

[0046] Example 2 200 kg of coal gasification black water flocculation liquid from a coal chemical enterprise in Ordos City was selected, and the mass concentration of the flocculation liquid was 8%; The coal gasification black water flocculated liquid is homogenized and dispersed and then concentrated by sedimentation to obtain a coal gasification black water concentrate having a mass concentration of 25%; Add dispersant sodium polyacrylate to the coal gasification black water flocculation liquid, the amount of dispersant added is 0.65% (0.104kg) of the dry matrix of the coal gasification black water flocculation liquid, and stir vigorously for 30 minutes; pump the stirred liquid to a wet vertical stirred mill, stir and mill for 45 minutes, and the particle size D90 of the solid particles in the milled liquid is 13.18μm and D50 is 3.82μm; pump the milled liquid to a high gradient magnetic separator for magnetic separation, the magnetic separation intensity is 1100 Gauss, the magnetic separation time is 2 minutes, and a suspension after magnetic separation is obtained; The pH value of the suspension after magnetic separation was adjusted to 9, and then stirred and aged at 40° C. for 1 hour. The aged system was sieved to obtain 64 kg of refined slurry, in which the particle size of the solid particles in the refined slurry was D90 of 13.18 μm, and the mass concentration of the refined slurry was 25%; The refined slurry was pumped into a flocculation agitator, and then 72 kg of natural rubber latex (mass concentration of 45%) was added; a 20% Al2(SO4)3 flocculant solution was added through a peristaltic pump, and flocculation copolymerization was carried out by stirring at 60°C until flocculation was terminated; the obtained liquid was filtered, washed with water three times, dried, and then dispersed to obtain a rubber composite powder; The obtained rubber composite powder is sequentially mixed and vulcanized to obtain the rubber composite material; Figure 4 This is the particle size distribution diagram of coal gasification black water concentrate after grinding.

[0047] Example 3 200 kg of coal gasification black water flocculant from a coal chemical enterprise in Ordos City was selected, and the mass concentration of the flocculant was 10%; The coal gasification black water flocculated liquid is homogenized and dispersed and then concentrated by sedimentation to obtain a coal gasification black water concentrate having a mass concentration of 20%; Add dispersant sodium polyacrylate to the coal gasification black water flocculation liquid, the amount of dispersant added is 0.65% (0.13kg) of the dry matrix of the coal gasification black water flocculation liquid, and stir vigorously for 30 minutes; pump the stirred liquid to a wet vertical stirred mill, stir and grind for 60 minutes, and the particle size D90 of the solid particles in the milled liquid is 11.2μm and D50 is 3.71μm; pump the milled liquid to a high gradient magnetic separator for magnetic separation, the magnetic separation intensity is 1200 Gauss, and the magnetic separation time is 1.5 minutes to obtain a suspension after magnetic separation; The pH value of the suspension after magnetic separation was adjusted to 9.5, and then stirred and aged at 45° C. for 1.5 hours. The aged system was sieved to obtain 100 kg of refined slurry, in which the particle size of the solid particles in the refined slurry was D90 of 11.2 μm, and the mass concentration of the refined slurry was 20%; The refined slurry is pumped into a flocculation agitator, and then 80 kg of natural rubber latex (mass concentration is 50%) is added; an Al2(SO4)3 flocculant solution with a mass concentration of 20% is added through a peristaltic pump, and flocculation copolymerization is carried out by stirring at 60°C until flocculation stops; the obtained liquid is filtered, washed with water three times, dried, and then dispersed to obtain a rubber composite powder; The obtained rubber composite powder is sequentially mixed and vulcanized to obtain the rubber composite material; Figure 5 This is the particle size distribution diagram of coal gasification black water concentrate after grinding.

[0048] Example 4 200 kg of coal gasification black water flocculant from a coal chemical enterprise in Ordos City was selected, and the mass concentration of the flocculant was 10%; The coal gasification black water flocculated liquid is homogenized and dispersed and then concentrated by sedimentation to obtain a coal gasification black water concentrate having a mass concentration of 25%; Add dispersant sodium polyacrylate to the coal gasification black water flocculation liquid, the amount of dispersant added is 0.7% (0.14kg) of the dry matrix of the coal gasification black water flocculation liquid, and stir vigorously for 30 minutes; pump the stirred liquid to a wet vertical stirred mill, stir and grind for 90 minutes, and the particle size D90 of the solid particles in the milled liquid is 10.98μm and D50 is 3.64μm; pump the milled liquid to a high gradient magnetic separator for magnetic separation, the magnetic separation intensity is 1000 Gauss, the magnetic separation time is 3 minutes, and a suspension after magnetic separation is obtained; The pH value of the suspension after magnetic separation was adjusted to 10, and then stirred and aged at 50° C. for 1.5 hours. The aged system was sieved to obtain 80 kg of refined slurry, in which the particle size of the solid particles in the refined slurry was D90 of 10.98 μm, and the mass concentration of the refined slurry was 25%; The refined slurry is pumped into a flocculation agitator, and then 100 kg of natural rubber latex (mass concentration is 40%) is added; a 20% Al2(SO4)3 flocculant solution is added through a peristaltic pump, and flocculation copolymerization is carried out by stirring at 60°C until flocculation stops; the obtained liquid is filtered, washed with water three times, dried, and then dispersed to obtain a rubber composite powder; The obtained rubber composite powder is sequentially mixed and vulcanized to obtain the rubber composite material; Figure 6 This is the particle size distribution diagram of coal gasification black water concentrate after grinding.

[0049] Example 5 200 kg of coal gasification black water flocculation liquid from a coal chemical enterprise in Ordos City was selected, and the mass concentration of the flocculation liquid was 8%; The coal gasification black water flocculated liquid is homogenized and dispersed and then concentrated by sedimentation to obtain a coal gasification black water concentrate having a mass concentration of 30%; Add dispersant sodium polyacrylate to the coal gasification black water flocculation liquid, the amount of dispersant added is 0.8% (0.128kg) of the dry matrix of the coal gasification black water flocculation liquid, and stir vigorously for 30 minutes; pump the stirred liquid to a wet vertical stirred mill, stir and grind for 90 minutes, and the particle size D90 of the solid particles in the milled liquid is 7.37μm and D50 is 2.74μm; pump the milled liquid to a high gradient magnetic separator for magnetic separation, the magnetic separation intensity is 1100 Gauss, the magnetic separation time is 1 minute, and a suspension after magnetic separation is obtained; The pH value of the suspension after magnetic separation was adjusted to 10, and then stirred and aged at 60° C. for 1 hour. The aged system was sieved to obtain 54 kg of refined slurry, in which the particle size of the solid particles in the refined slurry was D90 of 7.37 μm, and the mass concentration of the refined slurry was 30%; The refined slurry was pumped into a flocculation agitator, and then 71 kg of natural rubber latex (mass concentration of 45%) was added; an Al2(SO4)3 flocculant solution with a mass concentration of 20% was added through a peristaltic pump, and flocculation copolymerization was carried out by stirring at 60°C until flocculation was terminated; the obtained liquid was filtered, washed with water three times, dried, and then dispersed to obtain a rubber composite powder; The obtained rubber composite powder is sequentially mixed and vulcanized to obtain the rubber composite material; Figure 7 This is the particle size distribution diagram of coal gasification black water concentrate after grinding.

[0050] Example 6 200 kg of coal gasification black water flocculation liquid from a coal chemical enterprise in Ordos City was selected, and the mass concentration of the flocculation liquid was 7%; The coal gasification black water flocculated liquid is homogenized and dispersed and then concentrated by sedimentation to obtain a coal gasification black water concentrate having a mass concentration of 20%; Add dispersant sodium polyacrylate to the coal gasification black water flocculation liquid, the amount of dispersant added is 1% (0.14kg) of the dry matrix of the coal gasification black water flocculation liquid, and stir vigorously for 30 minutes; pump the stirred liquid to a wet vertical stirred mill, stir and grind for 90 minutes, and the particle size D90 of the solid particles in the milled liquid is 5.61μm and D50 is 2.06μm; pump the milled liquid to a high gradient magnetic separator for magnetic separation, the magnetic separation intensity is 1200 Gauss, the magnetic separation time is 2 minutes, and a suspension after magnetic separation is obtained; The pH value of the suspension after magnetic separation was adjusted to 10, and then stirred and aged at 65° C. for 1.5 hours. The aged system was sieved to obtain 70 kg of refined slurry, in which the particle size of the solid particles in the refined slurry was D90 of 5.61 μm, and the mass concentration of the refined slurry was 20%; The refined slurry was pumped into a flocculation agitator, and then 56 kg of natural rubber latex (mass concentration of 50%) was added; an Al2(SO4)3 flocculant solution with a mass concentration of 20% was added through a peristaltic pump, and flocculation copolymerization was carried out by stirring at 60°C until flocculation was terminated; the obtained liquid was filtered, washed with water three times, dried, and then dispersed to obtain a rubber composite powder; The obtained rubber composite powder is sequentially mixed and vulcanized to obtain the rubber composite material; Figure 8 This is the particle size distribution diagram of coal gasification black water concentrate after grinding.

[0051] Fig.12 This is a physical picture of rubber compound powder. Fig.13 This is a physical picture of the rubber composite material obtained after vulcanization. Fig.14 This is the SEM image of the rubber composite material obtained after vulcanization. Fig.15 TEM image of the rubber composite material obtained after vulcanization. Figures 12 to 15 It can be seen that the distribution of coal gasification fine slag in the powdered rubber is relatively uniform, without obvious agglomeration, and has good compatibility with the rubber matrix.

[0052] Comparative Example 1 200 kg of coal gasification black water flocculant from a coal chemical enterprise in Ordos City was selected, and the mass concentration of the flocculant was 7.5%; The coal gasification black water flocculated liquid is homogenized and dispersed and then concentrated by sedimentation to obtain a coal gasification black water concentrate having a mass concentration of 40%; Add dispersant sodium polyacrylate to the coal gasification black water flocculation liquid, the amount of dispersant added is 2% (0.3kg) of the dry matrix of the coal gasification black water flocculation liquid, and stir vigorously for 40 minutes; pump the stirred liquid to a wet vertical stirred mill, stir and grind for 3 minutes, and the particle size D90 of the solid particles in the milled liquid is 82.2μm; pump the milled liquid to a high gradient magnetic separator for magnetic separation, the magnetic separation intensity is 850 Gauss, the magnetic separation time is 3 minutes, and a suspension after magnetic separation is obtained; The pH value of the suspension after magnetic separation was adjusted to 11, and then stirred and aged at 35° C. for 0.5 h, and the supernatant of the aged system was poured out to obtain 37.5 kg of refined slurry, in which the particle size of the solid particles in the refined slurry was D90 of 82.2 μm, and the mass concentration of the refined slurry was 40%; The refined slurry was pumped into a flocculation agitator, and then 67 kg of natural rubber latex (mass concentration of 45%) was added; 25% Al2(SO4)3 flocculant solution was added through a peristaltic pump, and flocculation copolymerization was carried out by stirring at 60°C until flocculation was terminated; the obtained liquid was filtered, washed with water three times, dried, and then dispersed to obtain rubber composite powder; The obtained rubber composite powder is sequentially mixed and vulcanized to obtain the rubber composite material; Fig. 9 This is the particle size distribution diagram of coal gasification black water concentrate after grinding.

[0053] Fig.16 The SEM image of the rubber compound powder obtained is Fig.16 It can be seen from the cross-sectional morphology of the coal gasification slag rubber composite material at this time that due to the large particle size, the surface bonding ability is small and the bonding ability with rubber is poor.

[0054] Comparative Example 2 200 kg of coal gasification black water flocculation liquid from a coal chemical enterprise in Ordos City was selected, and the mass concentration of the flocculation liquid was 7%; The coal gasification black water flocculated liquid is homogenized and dispersed and then concentrated by sedimentation to obtain a coal gasification black water concentrate having a mass concentration of 20%; Add dispersant sodium polyacrylate to the coal gasification black water flocculation liquid, the amount of dispersant added is 0.5% (0.07kg) of the dry matrix of the coal gasification black water flocculation liquid, and stir vigorously for 20 minutes; pump the stirred liquid to a wet vertical stirred mill, stir and grind for 5 minutes, and the particle size D90 of the solid particles in the milled liquid is 79.06μm; pump the milled liquid to a high gradient magnetic separator for magnetic separation, the magnetic separation intensity is 900 Gauss, the magnetic separation time is 3 minutes, and a suspension after magnetic separation is obtained; The pH value of the suspension after magnetic separation was adjusted to 8, and then stirred and aged at 40° C. for 1.5 hours. The aged system was sieved to obtain 70 kg of refined slurry, in which the particle size of the solid particles in the refined slurry was D90 of 79.06 μm, and the mass concentration of the refined slurry was 20%; The refined slurry was pumped into a flocculation agitator, and then 56 kg of natural rubber latex (mass concentration of 50%) was added; 20% Al2(SO4)3 flocculant solution was added through a peristaltic pump, and flocculation copolymerization was carried out by stirring at 60°C until flocculation was terminated; the obtained liquid was filtered, washed with water three times, dried, and then dispersed to obtain rubber composite powder; The obtained rubber composite powder is sequentially mixed and vulcanized to obtain the rubber composite material; Fig.10 This is the particle size distribution diagram of coal gasification black water concentrate after grinding.

[0055] Comparative Example 3 200 kg of coal gasification black water flocculation liquid from a coal chemical enterprise in Ordos City was selected, and the mass concentration of the flocculation liquid was 8%; The coal gasification black water flocculated liquid is homogenized and dispersed and then concentrated by sedimentation to obtain a coal gasification black water concentrate having a mass concentration of 50%; Add dispersant sodium polyacrylate to the coal gasification black water flocculation liquid, the amount of dispersant added is 0.5% (0.08kg) of the dry matrix of the coal gasification black water flocculation liquid, and stir vigorously for 20 minutes; pump the stirred liquid to a wet vertical stirred mill, stir and grind for 120 minutes, and the particle size D90 of the solid particles in the milled liquid is 61.95μm; pump the milled liquid to a high gradient magnetic separator for magnetic separation, the magnetic separation intensity is 1500 Gauss, the magnetic separation time is 3 minutes, and a suspension after magnetic separation is obtained; The pH value of the suspension after magnetic separation was adjusted to 10, and then the suspension was stirred and aged at 50° C. for 1.5 hours. The aged system was sieved to obtain 32 kg of refined slurry, in which the particle size of the solid particles in the refined slurry was D90 of 61.95 μm, and the mass concentration of the refined slurry was 50%; The refined slurry is pumped into a flocculation agitator, and then 64 kg of natural rubber latex (mass concentration is 50%) is added; 20% Al2(SO4)3 flocculant solution is added through a peristaltic pump, and flocculation copolymerization is carried out by stirring at 60°C until flocculation stops; the obtained liquid is filtered, washed with water three times, dried, and then dispersed to obtain rubber composite powder; The obtained rubber composite powder is sequentially mixed and vulcanized to obtain the rubber composite material; Fig.11 This is the particle size distribution diagram of coal gasification black water concentrate after grinding.

[0056] Performance Testing Mechanical properties of the rubber composite materials obtained in Examples 1 to 6 and Comparative Examples 1 to 3 were tested, wherein the tensile strength was tested in accordance with the GB / T531-99 test standard, the tear strength was tested in accordance with the GB / T529-99 test standard, the modulus was tested in accordance with the GB / T531-99 test standard, and the elongation at break was tested in accordance with the GB / T531-99 test standard; The test results obtained are shown in Table 1; Table 1 Mechanical properties of rubber composite materials obtained in Examples 1 to 6 and Comparative Examples 1 to 3 It can be seen from Table 1 that the mechanical properties of Examples 1 to 6 are correlated with the particle sizes in the examples, and the smaller the particle size, the better the mechanical properties.

[0057] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a rubber composite material, characterized in that: The following steps are involved: The concentrated liquid obtained by concentrating the coal gasification black water flocculation liquid is mixed with a dispersant, and then subjected to grinding and magnetic separation in sequence to obtain a magnetically separated suspension; The suspension after magnetic separation is adjusted to be alkaline, and then aged and sieved in sequence to obtain a refined slurry; The refined slurry, rubber latex and flocculant are mixed and flocculated to obtain the rubber composite material.

2. The preparation method according to claim 1, characterized in that: The mass concentration of the concentrated solution is 15-45%; The dispersant includes one or more of sodium polyacrylate, sodium stearate, sodium hexametaphosphate, sodium tripolyphosphate and sodium citrate; The mass of the dispersant is 0.3-5.5% of the mass of the dry matrix of the concentrate.

3. The preparation method according to claim 1, characterized in that: The grinding time is 10 to 120 minutes.

4. The preparation method according to claim 1, characterized in that: The intensity of the magnetic separation is 800-1600 Gauss, and the time of the magnetic separation is 1-3 minutes.

5. The preparation method according to claim 1, characterized in that: The alkaline pH value is 8.5 to 11.0; The aging temperature is 35-65° C.; the aging is carried out under stirring, and the stirring time is 0.5-1.5 h.

6. The preparation method according to claim 1 or 5, characterized in that: The particle size D90 of the solid particles in the refined slurry is 2-18 μm.

7. The preparation method according to claim 1, characterized in that: The rubber latex comprises one or more of styrene-butadiene rubber latex, natural rubber latex and nitrile-butadiene rubber latex; The mass concentration of the rubber latex is 40-69%; The mass ratio of the dry matrix of the refined slurry to the solid in the rubber latex is 1:1.5-10.

8. The preparation method according to claim 1, characterized in that: The flocculant includes one or more of MgCl2, Mg(NO3)2, H2SO4, Mg(CH3COO)2, Al2(SO4)3 and KAl(SO4)2; The flocculant is mixed in the form of a flocculant solution, and the mass concentration of the flocculant solution is 15-20%.

9. The preparation method according to claim 1, characterized in that: The flocculation copolymerization temperature is 35-70° C., and the flocculation copolymerization is carried out under stirring conditions.

10. The preparation method according to claim 1, characterized in that: After the flocculation copolymerization, the obtained materials are mixed and vulcanized in sequence.

Citation Information

Patent Citations

  • Rubber and plastic filler preparation method, rubber and plastic filler, and use of filler

    CN107857900A

  • Pretreatment method for fine slag separation of coal gasification grey water

    CN108201970A

  • Method for preparing rubber filler by taking coal gasification slag as raw material

    CN112430400A

  • Method for preparing composite carbonaceous ultrafine powder material for rubber by utilizing gasified slag

    CN113480779A

  • Polymer functional filler prepared from fine coal gasification slag as well as preparation method and application of polymer functional filler

    CN116063740A